Dampak Pola Asuh Otoriter Orang Tua Terhadap Kepercayaan Diri Anak Didik - Asia, Asia; Cinta, Yesa; Kristiani, Kristiani (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This research aims to explore the impact of parents' authoritarian parenting styles on students' self-confidence, with a focus on understanding how this parenting approach influences children's psychological and emotional development. In this research, the author used a comprehensive literature review method, analyzing various previous studies that discussed the relationship between authoritarian parenting and children's self-confidence. This approach includes identifying the characteristics and aspects of authoritarian parenting, as well as the psychological impacts it produces, such as anxiety, fear of failure, and social withdrawal. By understanding this connection, it is hoped that this research can provide meaningful insight for parents, educators and other related parties regarding the importance of more democratic and supportive parenting. In addition, this research also aims to formulate effective intervention strategies to help children raised in authoritarian environments to develop healthy and positive self-confidence. It is hoped that the results of this research can contribute to improving parenting practices and creating a generation of children who are more confident, independent and able to face future challenges.